The Use of Virtual Media Laboratory to Increase Students’ Motivation on Direct Current Circuits Materials at Class X of MAN I Pekanbaru - Emhadelima Emhadelima (AT-TA'LIM, 2015)
The purpose of the study is to determine whether there is a significance effect on the use of Practicum methods by using Crocodile Program combined with lectures, question and answer activities give significant effect on  students’ activities in learning electricity simple lesson and to identify whether the use of the simulation lab provides better results than the traditional lab on learning outcomes. 36 natural science students was involved in the study. The data was analyzed by using t-test. The finding showed that the use of Practicum methods by using Crocodile Program combined with lectures; question and answer activities give significant effect on students’ activities in learning electricity simple lesson. The finding also showed that the use of the simulation lab can provide better results than the traditional lab on learning outcomes. It occurred when there is an adequate software capability and students can operate the software properly. Without taking into account about the cost of procurement of computers and software programs Crocodile, lab simulations are very low cost because it does not need to purchase laboratory equipment, supplies and other consumables. It is expected that Crocodile Program not only as a practical method to implement but also as a medium to explain the concepts of electronic circuits. Key words: Virtual Media, Circuits Materials.Copyright © 2015 by Al-Ta'lim All right reserved